Hepatic inflammation caused by dysregulated bile acid synthesis is reversible by butyrate supplementation. Issue 4 (1st November 2017) - Sheng, Lili; Jena, Prasant Kumar; Hu, Ying; Liu, Hui‐Xin; Nagar, Nidhi; Kalanetra, Karen M; French, Samuel William; French, Samuel Wheeler; Mills, David A; Wan, Yu‐Jui Yvonne
Abstract: Dysregulated bile acid (BA) synthesis or reduced farnesoid X receptor (FXR) levels are found in patients having metabolic diseases, autoimmune hepatitis, and liver cirrhosis or cancer. The objective of this study was to establish the relationship between butyrate and dysregulated BA synthesis‐induced hepatitis as well as the effect of butyrate in reversing the liver pathology. Wild‐type (WT) and FXR knockout (KO) male mice were placed on a control (CD) or western diet (WD) for 15 months. In the presence or absence of butyrate supplementation, feces obtained from 15‐month‐old WD‐fed FXR KO mice, which had severe hepatitis and liver tumors, were transplanted to 7‐month‐old WD‐fed FXR KO for 3 months. Hepatic phenotypes, microbiota profile, and BA composition were analyzed. Butyrate‐generating bacteria and colonic butyrate concentration were reduced due to FXR inactivation and further reduced by WD intake. In addition, WD‐fed FXR KO male mice had the highest concentration of hepatic β‐muricholic acid (β‐MCA) and bacteria‐generated deoxycholic acid (DCA) accompanied by serious hepatitis. Moreover, dysregulated BA and reduced SCFA signaling co‐existed in both human liver cancers and WD‐fed FXR KO mice. Microbiota transplantation using butyrate‐deficient feces derived from 15‐month‐old WD‐fed FXR KO mice increased hepatic lymphocyte numbers as well as hepatic β‐MCA and DCA concentrations. Furthermore, butyrate supplementation reduced hepatic β‐MCA as well as DCA and eliminated hepatic lymphocyte infiltration. In conclusion, reduced butyrate contributes to the development of hepatitis in the FXR KO mouse model. In addition, butyrate reverses dysregulated BA synthesis and its associated hepatitis. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.